Good Day: Aesthetic Perspectives on Audio Visual Coffee Advertisements - Wiki Riandi; Raihandhika Briliantana; Salsa Solli Nafsika (Universitas Pendidikan Indonesia, 2021)
Artwork in a beauty is a must in every process of creation. Art is one of the entertainment media, which can provide pleasure for the general public. One form of art that is often used as entertainment is art in the form of audio-visual. Advertising is one form of video that is found today, almost all digital media have visual advertisements. Be it on television, billboards or billboards, the internet, and much more. Advertising media using moving visuals is considered effective because it can attract the attention of consumers who see it and tend to feel at home watching it because it is not monotonous. Advertisements are made with the hope that consumers who see are able to feel even carried away and moved to buy the product itself. Ads are made very detailed with the intent and purpose for the promotion to run perfectly. The purpose of this study is to analyze and dissect an audio visual work in the type of good day coffee advertisement both in terms of audio and visual design and creation and then see whether this advertisement has been effective in terms of visual, audio, content, and duration.